Economic Theory of Fertility: Reply to Cullison - Leibenstein, Harvey (Quarterly Journal of Economics, 1977)
Journal Article Economic Theory of Fertility: Reply to Cullison Get access Harvey Leibenstein Harvey Leibenstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 91, Issue 2, May 1977, Pages 349–350, https://doi.org/10.2307/1885423 Published: 01 May 1977